Analisis Pengendalian Internal dalam Meningkatkan Efektivitas Pemberian Kredit Pada PT. Federal Internasional Finance Kabupaten Tolitoli - Fatimah, Fatimah (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of internal control on the effectiveness of credit disbursement at PT Federal Internasional Finance (FIF Group) in Tolitoli Regency. Using a quantitative method and simple linear regression analysis, this research involved 31 respondents consisting of employees engaged in the credit disbursement process. The results show that internal control significantly influences the effectiveness of credit disbursement, contributing 65.3%, while the remaining 34.7% is influenced by other factors. These findings confirm that an effective internal control system can enhance operational efficiency and minimize the risk of bad credit, thus supporting the company’s business sustainability.